Gasoline Prices and Their Relationship to Drunk-Driving Crashes - Angela Robertson
his study investigates the relationship between changing gasoline prices and drunk-driving crashes. Specifically, we examine the effects of gasoline prices on drunk-driving crashes in Mississippi by age, gender, and race from 2004Ð2008, a period experiencing great fluctuation in gasoline prices. An exploratory visualization by graphs shows that higher gasoline prices are generally associated with fewer drunk-driving crashes. Higher gasoline prices depress drunk- driving crashes among younger and older drivers, among male and female drivers, and among white, black, and Hispanic drivers. The statistical results suggest that higher gasoline prices lead to lower drunk-driving crashes for female and black drivers. However, alcohol consumption is a better predictor of drunk-driving crashes, especially for male, white, and older drivers.Drunk-driving crashes, gasoline prices, alcohol consumption, Mississippi